Self-reported previous experiences with sharks and stingrays predict behavioral intentions of tolerance: differential effects of wild versus captive marine predators - Gabriella M. Hancock; Katie D. Dudley; Dede Long; Christopher G. Lowe (Frontiers in Marine Science, 2024)
Previous research has shown that the general population are more likely to learn about certain species groups (such as sharks) from popular media as opposed to their own first-hand experience. Yet, personal encounters with these animals can drastically affect people’s beliefs and behaviors. This study surveyed 380 members of the public to assess their previous experience of encountering sharks and stingrays in the wild as well as at zoos and aquaria, and tested how said experiences influenced their behavioral intentions of tolerance for these particular elasmobranchs. Results indicated that self-reported experience having previously encountered these species groups in the wild was predictive of all assessed behavioral indicators of tolerance for sharks and rays. Self-reported previous encounters with captive animals were predictive of fewer behavioral intentions of tolerance, and only for the tolerance of sharks. Findings reveal the important role that first-hand interaction with these animals plays in humans’ tolerance to coexist and care for these animals and their habitat. Implications for conservation are discussed.